Ethics and aesthetics of translation : exploring the works of Atxaga, Kundera and Semprún - Hulme, Harriet (Literature and translation., 2018)
Ethics and Aesthetics of Translation engages with translation as part of an interrogation of ethical as well as political thought in the work of Atxaga, Kundera and Semprún. In approaching the work of these authors, it draws upon the approaches to translation offered by Benjamin, Derrida, Ricœur and Deleuze to highlight broad ethical questions.